John Dearness (1852-1954) : Canadian pioneer mycologist-plant pathologist - Estey, R.H. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1993)
John Dearness, a professional educator who became the first internationally acknowledged Canadian-born mycologist, was also a largely self-taught pioneer plant pathologist. His ability to isolate and identify plant parasitic fungi, and his readiness to assist professional plant pathologists, became so widely known that he was elected President of the Canadian Division of the American Phytopathological Society. The Canadian Phytopathological Society, of which he was a charter member, made him an honorary member. Many more honors were conferred on this remarkable man in recognition of his contributions to botany, mycology, and plant pathology in Canada.